Role of luxS in immune evasion and pathogenicity of piscine Streptococcus agalactiae is not dependent on autoinducer-2. Issue 99 (April 2020) - Cao, Qing; Ma, Ke; Nie, Meng; Dong, Yuhao; Lu, Chengping; Liu, Yongjie
Abstract: luxS-mediated autoinducer 2 (AI-2)-dependent quorum sensing (QS) has been demonstrated to affect many bacterial phenotypes, including virulence. Streptococcus agalactiae harbors a functional luxS gene required for the biosynthesis of AI-2. In this study, we investigated the regulation effect and mechanism of the luxS /AI-2 QS system in the pathogenicity of the piscine S. agalactiae strain GD201008-001. We found that inactivation of luxS caused a marked decrease in biofilm formation, hemolytic activity, antiphagocytosis and intracellular survival of S. agalactiae . Except for hemolytic activity, the altered phenotypes due to the luxS deletion were AI-2-independent. Further investigation indicated that high levels of the proinflammatory cytokines IL-1β and IL-6 could be induced in macrophages co-incubated with the luxS deletion mutant and synthetic AI-2, single or combined. Also, the results of tilapia infection showed that inactivation of luxS significantly decreased the virulence of S. agalactiae but upregulated the expression of cytokines in spleens and brains. Increased proinflammatory effects of the luxS mutant were restored in the luxS complemented strain but could not be restored by AI-2 addition. All the findings suggest that luxS is involved in virulence-associated phenotypes and immunological evasion of S. agalactiae, and furthermore, this involvement is mostly AI-2-independent. This study will provide valuable insights into our understanding of the role of the LuxS/AI-2 QS system in the pathogenesis of S. agalactiae . Highlights: Inactivation of luxS caused virulence decrease in the piscine S. agalactiae strain GD201008-001. Both luxS deletion and AI-2 addition induced high expression levels of the proinflammatory cytokines in macrophages. Most of altered phenotypes due to the luxS deletion were AI-2-independent.